High Ni and low Mn/Fe in olivine phenocrysts of the Karoo meimechites do not reflect pyroxenitic mantle sources - Heinonen, Jussi S.; Fusswinkel, Tobias (Chemical Geology, 2017)
Nickel contents and Mn/Fe in olivine phenocrysts have been suggested to reflect the mineral composition of the mantle source of the host magma. This hypothesis is tested here against a well-characterized suite of meimechitic (or Ti-rich komatiitic) dikes from the Antarctic extension of the Jurassic ~180 Ma Karoo large igneous province. The presented trace element data on Fo82–92 olivines show relatively high Ni (2430–3570 ppm) and low 100*Mn/Fe (1.32–1.5; Mn = 890–1570 ppm), compatible with pyroxenite-rich sources (Xpx = 37–75%). Many other mantle source indicators (parental melt MgO and whole-rock Zn/Fe, MgO/CaO, FC3MS, Zr/Y vs. Nb/Y, and radiogenic isotope compositions) suggest dominantly or solely peridotitic mantle sources, however. Therefore, the measured high Ni and low Mn/Fe are likely to reflect high temperatures and pressures of melting and possibly high water contents in such peridotite sources. We recommend considerable caution when using Ni and Mn contents of olivine as source indicators, as they may only serve for qualitative comparison of primitive volcanic rocks that originated under fairly similar mantle conditions. Peer reviewed